FULLNESS AND EMPTINESS IN BONAVENTURE AND ECKHART - Cousins, Ewert (Journal of Dharma, 1981)
The tension between negative and positive theology permeated the thought of Western Christianity in thë High Middle Ages. Medievtl writers found their classical source for these two approaches in the writings of the Pseudo-Dionysius, whose works had been introduced into the West by the translations of John Scotus Erigena in the ninth century. The via positiva was explored extensively in The Divine Names, on which Thomas Aquinas wrote a commentary and which povided the basis for his treatment of our knowledge of God's attributes in the early questions of the Summa theologiae. The via negatiya was formulated much more concisely in The Mystical Theology, which influenced Bonaventure in his final stage of The Sou I's Journey into God and the author of The Cloud of Unknowing in formulating his methcd of contemplation.